Grammatical Categories : Semantics and Pragmatics at the Crossroads - Žic Fuchs, Milena (Array, 2014)
The interrelationship between semantics and pragmatics has been a much discussed topic in linguistics. The intricacies of this relationship have also been viewed with regard to the role of pragmatics in determining the meaning of conventionalized grammatical categories/structures/constructions. In fact, the relationship between semantics and pragmatics from the point of view of grammatical categories highlights and unveils the complexity that can exist between semantic and pragmatic phenomena. In simple terms, we find two main views on this issue: 1. the view that pragmatics lies completely outside of grammatical categories, and 2. the view that pragmatics cannot be divorced from the meaning structure of grammatical categories in some cases. These opposed views are not simply a theoretical issue, but often result in different classifications of various grammatical phenomena, as well as their interpretation within grammars and linguistic textbooks in general. This paper will address the above interface on the basis of concrete syntactic/morphological grammatical constructions in English and Croatian with the aim of showing that pragmatics should be viewed as a multi-layered phenomenon, which can be seen in part residing “outside of grammatical categories”, but at the same time, at least in some cases, can also be seen as an integral part of the semantic structure of a grammatical construction. The different views are not important only in a grammatical sense, but they also bring into focus the question as to how convention arises, and what the basic tenets of conventionalization of grammatical categories can be. With the notion of convention in view, some basic postulates of the so-called Relevance Theory (Sperber and Wilson 1995), as well as the well-known Gricean (Grice 1975) claims on human communication, will be analyzed.